2020
DOI: 10.1007/s12264-020-00544-0
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage–NLRP3 Inflammasome Activation Exacerbates Cardiac Dysfunction after Ischemic Stroke in a Mouse Model of Diabetes

Abstract: Ischemic stroke is one of the leading causes of death worldwide. In the post-stroke stage, cardiac dysfunction is common and is known as the brain-heart interaction. Diabetes mellitus worsens the post-stroke outcome. Stroke-induced systemic inflammation is the major causative factor for the sequential complications, but the mechanism underlying the brain-heart interaction in diabetes has not been clarified. The NLRP3 (NLR pyrin domain-containing 3) inflammasome, an important component of the inflammation after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…The type 2 diabetic mouse model was generated as described previously (Lin et al, 2020 ). Briefly, we first fed each mouse on a high-fat diet (Guangdong Medical Laboratory Animal Center, Guangzhou, China) for 3 w. A dose of 100 mg/kg streptozotocin (STZ, Sigma, St. Louis, MO, USA) was then injected intraperitoneally.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The type 2 diabetic mouse model was generated as described previously (Lin et al, 2020 ). Briefly, we first fed each mouse on a high-fat diet (Guangdong Medical Laboratory Animal Center, Guangzhou, China) for 3 w. A dose of 100 mg/kg streptozotocin (STZ, Sigma, St. Louis, MO, USA) was then injected intraperitoneally.…”
Section: Methodsmentioning
confidence: 99%
“…The ischemic stroke mouse model was generated by MCAO following the protocol of our previous study (Lin et al, 2020 ). In brief, mice were anesthetized with 2% isoflurane (RWD Life Science Co., Ltd, Shenzhen, China).…”
Section: Methodsmentioning
confidence: 99%
“…A recently developed NLRP3 inhibitor, CY-09, binds directly to the ATP-binding motif of the NACHT domain, thus inhibiting NLRP3 assembly and ATPase activity. Its therapeutic efficacy has been tested on animal models of CAPS and type 2 diabetes [ 117 ]. The use of CY-09 in a mouse model of diabetic stroke was able to protect from cardiac dysfunction associated with diabetic ischemic stroke [ 118 ].…”
Section: Nlrp3 Inflammasome As a Target For Pharmacological Inhibimentioning
confidence: 99%
“…Diabetes increases the incidence of cardiac complications after IS, which manifest as myocardial infarction, congestive heart failure (85), arrhythmia, cardiac arrest (16), and exacerbate mortality and worse neural prognosis in the post-stroke state (15,49,86). Burkot et al have reported that heart failure occurrence rate after IS is 22.3% in diabetic patients and 15.1% without diabetes (10).…”
Section: Diabetic Status Exacerbates Cerebral-cardiac Syndrome Clinical Evidencementioning
confidence: 99%
“…Inflammation is an important trigger for both diabetes and CCS (11,12), and NOD-like receptor pyrin domain containing 3 (NLRP3) inflammasome is the crucial element to promote the maturation and release of IL-1b and IL-18 (13). Recent studies have indicated the role of NLRP3 inflammasome in diabetes and diabetic CCS (14,15). Therefore, the responsible pathway of NLRP3 inflammasome activation and subsequent effects on diabetic CCS need further exploration.…”
Section: Introductionmentioning
confidence: 99%